2014
DOI: 10.1530/rep-13-0104
|View full text |Cite
|
Sign up to set email alerts
|

Follicle development, endocrine profiles and ovulation rate in adult Merino ewes: effects of early nutrition (pre- and post-natal) and supplementation with lupin grain

Abstract: In adult ewes, we tested whether ovarian function, including the response to short-term supplementation, was affected by the nutrition of their mothers during the pre-/post-natal period. A 2!2 factorial design was used with nutrition in early life (low or high) and a 6-day supplement (with or without) as factors. All ewes received three prostaglandin (PG) injections 7 days apart, and the supplement (lupin grain) was fed for 6 days from 2 days after the second until the third PG injection. We measured reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The concentration of oestradiol-17β was suppressed in the control ewes on day 3 relative to day -4, but lupin did not affect this hormone concentration in this study, which is consistent with the observations of Somchit et al (14) after an intravaginal progestagen sponge treatment, but contrary to the studies of Viñoles et al (27), who observed increased concentrations of oestradiol using a different experimental model. It can be suggested that oestradiol is affected by IGF-I and that these hormones are reciprocally modulated, as observed in ewes in oestrous season (15,18,20).…”
Section: Discussionsupporting
confidence: 92%
“…The concentration of oestradiol-17β was suppressed in the control ewes on day 3 relative to day -4, but lupin did not affect this hormone concentration in this study, which is consistent with the observations of Somchit et al (14) after an intravaginal progestagen sponge treatment, but contrary to the studies of Viñoles et al (27), who observed increased concentrations of oestradiol using a different experimental model. It can be suggested that oestradiol is affected by IGF-I and that these hormones are reciprocally modulated, as observed in ewes in oestrous season (15,18,20).…”
Section: Discussionsupporting
confidence: 92%
“…Not only different energy levels but also some components of the diet, such as protein or urea concentrations, or the addition of supplements (e.g., lupin grain and barley, and/or citrus-beet pulp concentrate) may affect reproductive function of livestock species [3,11,20,23,24]. Arginine (Arg), an amino acid and a possible supplement, has been recently reported to improve reproductive performance and the uterine environment for the maintenance of pregnancy in sheep [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Failure to detect changes in follicle numbers may have been due to the short duration on the diet or conducting follicle counts too soon after beginning estradiol treatment. Visible follicle numbers are an indicator of ovarian follicle reserve status in cattle (Ireland et al, 2009), and links between gestational nutrition and ovarian follicle reserve status are evident in sheep and cattle (Evans et al, 2012;Viñoles et al, 2013). However, no evidence exists to indicate that visible follicle numbers or the underlying ovarian follicle reserve can be adversely affected in the early postnatal period; no such detrimental effects could be detected in this work.…”
Section: Discussionmentioning
confidence: 69%